A decade of improvements in equity of access to reproductive and maternal health services in Cambodia, 2000-2010. - Dingle, A; Powell-Jackson, T; Goodman, C (2013)
INTRODUCTION: Despite encouraging reductions in global maternal mortality rates, Millennium Development Goal (MDG) 5 on reducing maternal mortality and achieving universal access to reproductive health remains the most off-track of all MDGs. Furthermore a preoccupation with aggregate coverage statistics masks extensive disparities in health improvements between societal groups. Recent national health indicators for Cambodia highlight impressive improvements, for example, in maternal, infant and child mortality, whilst substantial government commitments have been made since 2000 to address health inequities. It is therefore timely to explore the extent of equity in access to key reproductive and maternal health services in Cambodia and how this has changed over time. METHODS: Analysis was conducted on three rounds of Demographic and Health Survey data from 2000, 2005 and 2010. Outcome variables comprised utilisation of six reproductive and maternal health services--antenatal care, skilled birth attendance, facility-based delivery, postnatal care, met need for family planning and abortion by skilled provider. Four equity measures were calculated--equity gaps, equity ratios, concentration curves and concentration indices. Household assets were used to create the social-stratification variable, using principal components analysis. RESULTS: Coverage levels of all six services improved over the decade. Coverage improvements were greatest amongst wealthier quintiles of the population, although poorer quintiles also increased use of services. Critically, inequity in service use of all services dramatically reduced over time, except for postnatal care where inequity increased slightly. However, in 2010 inequity in service use remained favouring wealthier quintiles, greatest in use of skilled birth attendance and facility-based delivery, though the magnitude of inequity was substantially reduced compared to 2000. Met need for family planning was almost perfectly equitable in 2010. CONCLUSIONS: Cambodia has made impressive improvements in overall coverage of reproductive and maternal health services over the last decade, and also in the distribution of their use across wealth quintiles. A range of pro-poor health financing and supply-side policies as well as non-health factors may have contributed to these achievements. Further research will explore specific schemes qualitatively and quantitatively to assess their impact on equity and service use.